Development and characterization of winged bean (Phosphocarpus tetragonolobus L.) crackers. - Geganzo, Jesette Therese Genovate (2017.)
The study focused on the development of Winged Bean Crackers. Winged bean powder from the matured seeds used as substitute for flour in making crackers. The crackers were processed at varying winged bean powder concentrations based on the combine weight of the all-purpose flour and the winged bean powder. Three (3) formulations (WBC1 - 10%, WBC - 20% and WBC 3 - 30%) were subjected to sensory evaluation for General Preference test. The lowest sum of ranks from the three formulations was considered as the most Preferred Winged Bean Cracker. WBC2 with 20% winged bean powder, was considered as the Most Preferred Formulation through sensory evaluation by 30 panelists. For the general acceptability test, the Most Preferred Formulation was rated ?Like moderately? by 47% responses of the 30 panelists. No significant difference between the three formulations was reported after analyzing using Kruskal-Wallis Test at 5% level of significance. Proximate composition and iron content were determined in the winged bean powder, most preferred winged bean crackers and the control. Significant increases in the content of crude protein, crude fat, crude fiber and crude ash between the Most Preferred Formulation and the Control was observed using T-Test at P = 0.05. The addition of winged bean powder reported significantly increased the proximate composition of the crackers between the winged bean powder and control. Aside from the crackers, the winged bean powder contained 7.3% moisture, 17.8% protein, 20.1%, 8.8% fiber, 11.2% ash content 0.296 iron content. Addition of 20% winged bean powder improved the nutritional value of crackers and was ?Liked moderately?.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Crackers; Winged bean; Phosphocarpus tetragonolobus L